Answer:
x = 14
Step-by-step explanation:
the expression takes the form of a radical surd. to solve a radical surd we need to isolate the expression with the root from those not under the root sign
first;
this a surd, so
to eliminate the root we need to multiply it by an expression that will take it away,
since a root is the same as a power of half ()^1/2, then multiplying a half by two will make it one
we need to square both sides to eliminate the root
x -5 = (-3)^2
make x subject
x = 9 + 5
x = 14